A Stock Dividend Model Applying the Value Creation Approach in Iran’s Capital Market: The Generalized Method of Moments - Ebrahim Solati Khosroshahi; Younes Badavar Nahandi; Houshang Taghizadeh (تحقیقات مالی)
ObjectiveOne of the important concerns of managers and economic policymakers is the identification of stock dividend determinants. Therefore, this study explores the internal and external determinants of stock dividends among corporations listed on the Tehran Stock Exchange from 2009 to 2021. Additionally, this research aims to design a suitable model of stock dividends for Iran’s capital market by considering the value creation approach. MethodsIn the initial phase, all potential determinants of stock dividends were extracted by reviewing the extant literature, theories, and expert opinions. Subsequently, in the second phase, variables exhibiting a significant relationship with stock dividend ratio measures (including DPS to Price ratio, DPS to Sales revenue ratio, and DPS to EPS ratio) in Iran’s capital market were identified. In the third phase, the creation and examination of various models for stock dividends, resulting from different combinations of explanatory variables, were undertaken. It should be noted that the model is fitted by using the dynamic econometrics approach of the Generalized Moments Method. In the next phase, stock dividend models that maximize value creation for firms and stockholders were selected. Finally, the accuracy of the models in identifying companies with a propensity to distribute dividends above or below the expected level was tested. ResultsThe findings of this study indicate that the optimal model for stock dividends is the DPS to EPS ratio, comprising 11 explanatory variables selected from a pool of 36 variables. Using this model for stock dividends leads to the creation of maximum value for firms and stockholders. According to the extracted model, monopoly in the product market, operating cash flows, cash level, sales growth, and economic growth positively affect stock dividends. The stock dividend of the previous period, financial leverage, growth opportunities, changes in net working capital, uncertainty of cash flows, and inflation rate negatively impact stock dividends. This model was validated using the value creation approach test. Moreover, the accuracy of the extracted model in identifying companies with a propensity to distribute dividends above and below the expected level is 84% and 91%, respectively. ConclusionTo have a suitable stock dividend policy, managers should consider sales growth, uncertainty of cash flows, operating cash flows, financial leverage, cash level, growth opportunities, and changes in net working capital as internal factors. The structure of the industry, its level of monopoly, macroeconomic conditions such as inflation rate, and economic growth should be considered as external factors. Adopting such a stock dividend policy results in the creation of maximum value for both the firm and its shareholders.